IDENTIFIKASI KESEHATAN POHON DI KAWASAN PENGAMATAN BURUNG BIDADARI KECAMATAN JAILOLO SELATAN KABUPATEN HALMAHERA BARAT: Tree Health Identification in Burung Bidadari Area South Jailolo District West Hamahera Regency - Nurhikmah; Musi, Klaudia; Irmayanti, Laswi (Jurnal Forest Island, 2025)
Trees are said to be healthy if they can carry out physiological functions and have an ecological ecology from various disturbances. The decline in tree health can be seen based on the condition of tree damage. This study aims to determine the health condition of trees and the type of damage in the Burung Bidadari Area, South Jailolo District, West Halmahera Regency. The study was conducted in September-October 2024. The method used is FHM (Forest Health Monitoring). Observations were made in two different clusters, namely cluster 1 Block A2 (production forest), cluster 2 Block A3 (protected forest). The level of tree health was analyzed according to the level of damage calculated based on the TLI and TDLI categories. Based on the results of the study, there were 3 families, 3 types of trees. There were 9 types of damage, namely Konk, growing konk, growing fruit with a total of 1 case. Open wounds with a total of 1 case. Resinosis/gymosis with a total of 2 cases. Termite nests with a total of 1 case. Loss of dominant tip, dead tip with a total of 2 cases. Broken or dead branches with a total of 7 cases. Damaged leaves, buds or tuna with a total of 13 cases. Leaves with non-green fruit with a total of 17 boxes. The results of the Tree Level Index (TLI) determine that cluster 1 is included in the healthy class (0≤5) and cluster 2 is included in the healthy class (6-10).